Coagulation and inflammation in long‐term cancer survivors: results from the adult population. (14th March 2018) - Panova‐Noeva, M.; Schulz, A.; Arnold, N.; Hermanns, M. I.; Prochaska, J. H.; Laubert‐Reh, D.; Spronk, H. M.; Blettner, M.; Beutel, M.; Pfeiffer, N.; Münzel, T.; Lackner, K. J.; et al.
Abstract : Essentials The increase of cancer survival remains curtailed by cardiovascular mortality. We studied a large range of inflammatory and coagulation biomarkers in long‐term cancer survivors. Cancer history has an important impact on mortality independent of cardiovascular risk factors. Fibrinogen and von Willebrand factor are potential biomarkers in survivors of increased mortality. Summary: Background: The advances in cancer treatment and detection of early cancer have resulted in a steady increase in the number of of cancer survivors over the years. However, because of the long‐term toxic effects of chemotherapy and radiotherapy, the incidence of cardiovascular disease (CVD) is increasing in survivors. Objectives: To investigate traditional cardiovascular risk factors (CVRFs), inflammation and the coagulation profile in long‐term cancer survivors (cancer diagnosis ≥ 5 years) from a large adult population‐based study sample. Methods: The presence of cardiovascular risk factors (CVRFs) and laboratory markers were compared in individuals with ( n = 723) and without ( n = 13626) a long‐term history of cancer from the Gutenberg Health Study. Data on coagulation factors, D‐dimer and von Willebrand factor (VWF) activity were available for 4974 individuals ( n = 244 cancer survivors). Results: In multivariable regression models, a history of cancer was, independently of CVRFs and CVD, associated with higher fibrinogen levels ( β 6.99, 95% confidence interval [CI] 1.16–12.8), VWF activity ( β 5.08, 95% CI 0.02–10.1), and antithrombin activity ( β 1.85, 95% CI 0.44–3.27). Cancer survivors with CVD showed notably higher VWF activity than individuals with CVD without a history of cancer, with a difference in the means of 23.0 (7.9–38.1). Multivariate Cox regression analysis, adjusted for CVRFs, confirmed that a long‐term history of cancer is associated with a 72% higher mortality. Increased mortality in cancer survivors was dependent on fibrinogen level and VWF activity level. Conclusion: Cancer survivors showed a worse inflammation and coagulation profile than individuals without a history of cancer. Overall mortality in long‐term cancer survivors was increased independently of traditional CVRFs. These results underline the need to further investigate plasma biomarkers as complementary cardiovascular risk predictors in cancer survivors.